Smoking as a factor influencing the rehabilitation process after cardiac surgery - Alicja Mińko; Zuzanna Hilicka; Dominik Turzyński (Kazimierz Wielki University, 2021)
Introduction: Comprehensive cardiac rehabilitation is a standard therapeutic procedure in patients after cardiac surgery. Its course depends on many factors. One of them is smoking. Exposure of the body to tobacco compounds reduces the supply of oxygen to the organs, which in turn has a damaging effect on the heart tissue. Objective: The aim of this study is to determine the effect of smoking on the effectiveness of rehabilitation in patients after cardiac surgery. Materials and methods: The research was carried out at the Department of Cardiac Surgery, SPSK 2, Pomeranian Medical University in Szczecin. The research was conducted among 35 patients, divided into 3 groups. The first group of 9 people (26%) were non-smokers. The second group was assigned to 11 people (31%) who were heavy smokers. The third group consisted of 15 people (43%) who had been addicted to cigarettes in the past. The research tool used in the study was the 6-minute walk test. Results: Non-smokers achieved a greater improvement in the 6-minute test score compared to the group of smokers and ex-smokers, whose mean score was lower by 39.17 m (± 100.80) and 85.74 m (± 80.56), respectively. Conclusion: Smoking may have an impact on the exercise capacity and exercise tolerance in patients after cardiac surgery.